2013
DOI: 10.1161/atvbaha.113.301397
|View full text |Cite|
|
Sign up to set email alerts
|

Angptl3 Deficiency Is Associated With Increased Insulin Sensitivity, Lipoprotein Lipase Activity, and Decreased Serum Free Fatty Acids

Abstract: Objective-Angiopoietin-like 3 (Angptl3) is a regulator of lipoprotein metabolism at least by inhibiting lipoprotein lipase activity. Loss-of-function mutations in ANGPTL3 cause familial combined hypolipidemia through an unknown mechanism. Approach and Results-We compared lipolytic activities, lipoprotein composition, and other lipid-related enzyme/lipid transfer proteins in carriers of the S17X loss-of-function mutation in ANGPTL3 and in age-and sex-matched noncarrier controls. Gel filtration analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
141
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(156 citation statements)
references
References 32 publications
13
141
0
2
Order By: Relevance
“…In particular, we found that, compared with noncarriers, homozygotes, but not heterozygotes, displayed a 3-fold higher postheparin LPL activity. Moreover, we also observed that the homozygotes had reduced fasting plasma levels of FFAs and lower homeostasis model assessment of insulin resistance compared with control subjects (17). Based on these findings, it is reasonable to postulate that complete ANGPTL3 deficiency would cause accelerated postprandial clearance of TRLs, an effect that might be potentially implicated in FHBL2 hypolipidemia.…”
Section: Ofttsupporting
confidence: 52%
See 1 more Smart Citation
“…In particular, we found that, compared with noncarriers, homozygotes, but not heterozygotes, displayed a 3-fold higher postheparin LPL activity. Moreover, we also observed that the homozygotes had reduced fasting plasma levels of FFAs and lower homeostasis model assessment of insulin resistance compared with control subjects (17). Based on these findings, it is reasonable to postulate that complete ANGPTL3 deficiency would cause accelerated postprandial clearance of TRLs, an effect that might be potentially implicated in FHBL2 hypolipidemia.…”
Section: Ofttsupporting
confidence: 52%
“…It has been proposed that low LDL might be due to reduced VLDL to LDL conversion (14), even though an increased clearance rate of LDL particles has been observed in homozygous individuals (13). Reduced HDL has been explained by elevated endothelial lipase activity in the absence of ANGPTL3 (16), but the direct in vivo demonstration of this mechanism in FHBL2 subjects is lacking (17). Therefore, the full effect of ANGPTL3 on lipoprotein metabolism is likely to be very complex and is not yet fully understood.…”
Section: Ofttmentioning
confidence: 99%
“…It seem interesting to consider this observation in the light of results by Romeo et al ( 28 ) that reported in a population study higher prevalence of nonsynonymous (probably inactivating) variations in the ANGPTL3 genes among subjects in the lowest quartile of blood glucose levels. Moreover, we recently reported that FHBL2 homozygotes showed lower plasma levels of insulin and lower degree of insulin-resistance as estimated HOMA-IR index ( 36 ). If further confi rmed in additional investigations, these fi ndings could highlight a more comprehensive role of ANGPTL3 in regulating not only lipid but also glucose metabolism.…”
Section: Discussionmentioning
confidence: 70%
“…Many studies in humans, mice and livestock have shown that ANGPTL3 is involved in the regulation of lipid, glucose metabolism and energy balance (Kadomatsu et al, 2011;Arca et al, 2013;Robciuc et al, 2013). Accumulating evidence indicates that some genes closely related to ANGPTL3, especially LXRα, ANGPTL4 and ANGPTL6, function as a new class of lipid and energy metabolism modulator (Kadomatsu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Romeo et al (2009) also noted that a genetic variation of ANGPTL3 was associated with the lowest quartile of blood glucose levels. Therefore, ANGPTL3 appears to have an important role in lipoprotein, FFA and glucose metabolism (Robciuc et al, 2013).…”
Section: Introductionmentioning
confidence: 99%